2012
DOI: 10.3892/ijo.2012.1361
|View full text |Cite
|
Sign up to set email alerts
|

Pathway simulations in common oncogenic drivers of leukemic and rhabdomyosarcoma cells: A systems biology approach

Abstract: Abstract. A part of current research has intensively been focused on the proliferation and metabolic processes governing biological systems. Since the advent of high throughput methodologies such as microarrays, the load of genomic data has increased geometrically and along with that the need for computational methods to interpret these data. In the present study, we investigated in vitro the common proliferation and metabolic processes, associated with common oncogenic pathways, as far as gene expression is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 90 publications
(94 reference statements)
1
10
0
Order By: Relevance
“…The increasingly systematic nature of random mutagenesis and mutation identification, targeted mutagenesis/ cloning and identification of epigenetic modifications along with increasing computational power and variety of bioinformatic approaches are facilitating these efforts. Systems biological approaches can be used to model metabolic pathways, dynamics of specific cell behavior under varying stimuli, disease causing aberrations in functional networks and in screening for potential therapeutic agents (Chen et al, 2012;Lambrou et al, 2012;Nagasaki et al, 2011;Tan et al, 2013). These approaches can also demonstrate the consequences of nonsynonymous DNA polymorphisms on protein interactions and identify mutations leading to development of diseases (Reimand and Bader, 2013;Yates and Sternberg, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…The increasingly systematic nature of random mutagenesis and mutation identification, targeted mutagenesis/ cloning and identification of epigenetic modifications along with increasing computational power and variety of bioinformatic approaches are facilitating these efforts. Systems biological approaches can be used to model metabolic pathways, dynamics of specific cell behavior under varying stimuli, disease causing aberrations in functional networks and in screening for potential therapeutic agents (Chen et al, 2012;Lambrou et al, 2012;Nagasaki et al, 2011;Tan et al, 2013). These approaches can also demonstrate the consequences of nonsynonymous DNA polymorphisms on protein interactions and identify mutations leading to development of diseases (Reimand and Bader, 2013;Yates and Sternberg, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous occurrence of these cancers points to an underlying genetic event affecting two entirely different lineages. Review of literature revealed study comparing the expression profiles of Precursor T cell lymphoblastic leukemia and RMS cell lines and identified common oncogenic driving forces which were responsible for the progression of cancer cells [7]. Both muscle and hematopoietic stem cells arise from the embryonal mesoderm.…”
Section: Discussionmentioning
confidence: 99%
“…Both muscle and hematopoietic stem cells arise from the embryonal mesoderm. Further differentiation enables the two cell types to possess different functions and roles by differential gene regulation [7]. An early mutation occurring during embryonal development may predispose the individual for double malignancies involving the tissue types which develop from the mesoderm.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a computational approach, using cDNA microarrays, in order to identify commonalities between T-cell acute lymphoblastic leukemia (CCRF-CEM) and the embryonal rhabdomyosarcoma (TE-671) cell line predicted that JAK1, STAT1, PIAS2 and CDK4 are the driving forces that transform physiological cells to malignant 96 .…”
Section: Jrpmsmentioning
confidence: 99%